Orosomucoid 1 is involved in the development of chronic allograft rejection after kidney transplantation. (13th January 2020) - Higuchi, Haruka; Kamimura, Daisuke; Jiang, Jing-Jing; Atsumi, Toru; Iwami, Daiki; Hotta, Kiyohiko; Harada, Hiroshi; Takada, Yusuke; Kanno-Okada, Hiromi; Hatanaka, Kanako C; Tanaka, Yuki; Shinohara, Nobuo; et al.
Abstract : How orosomucoid 1 is involved in chronic allograft rejection Abstract: Chronic allograft rejection is the most common cause of long-term allograft failure. One reason is that current diagnostics and therapeutics for chronic allograft rejection are very limited. We here show that enhanced NFκB signaling in kidney grafts contributes to chronic active antibody-mediated rejection (CAAMR), which is a major pathology of chronic kidney allograft rejections. Moreover, we found that urinary orosomucoid 1 (ORM1) is a candidate marker molecule and therapeutic target for CAAMR. Indeed, urinary ORM1 concentration was significantly higher in kidney transplant recipients pathologically diagnosed with CAAMR than in kidney transplant recipients with normal histology, calcineurin inhibitor toxicity, or interstitial fibrosis and tubular atrophy. Additionally, we found that kidney biopsy samples with CAAMR expressed more ORM1 and had higher NFκB and STAT3 activation in tubular cells than samples from non-CAAMR samples. Consistently, ORM1 production was induced after cytokine-mediated NFκB and STAT3 activation in primary kidney tubular cells. The loss- and gain-of-function of ORM1 suppressed and promoted NFκB activation, respectively. Finally, ORM1-enhanced NFκB-mediated inflammation development in vivo . These results suggest that an enhanced NFκB-dependent pathway following NFκB and STAT3 activation in the grafts is involved in the development of chronic allograft rejection after kidney transplantation and that ORM1 is a non-invasive candidate biomarker and possible therapeutic target for chronic kidney allograft rejection.